Agenciamentos rizomáticos no currículo de educação física da cidade de São Paulo - Dias, Alessandra Aparecida (2024)
The objects of study were the curriculum and practices of physical education teachers. It aimed to investigate the processes of formulation and implementation of curricular policies, specifically the physical education curriculum in the universe of the Regional Directorate – Butantã, of the Municipal Department of Education of São Paulo. From these objects, some concerns emerged, which motivated and directed the research problem: How does the curricular policy act on the teaching practice? Do the effects enhance lives? With the questions presented, the general objective of the investigation was delimited: To understand how physical education teachers, who work in elementary school, incorporate the guidelines of the City Curriculum and express them in their daily practice. The specific objectives were delimited as follows: 1) To understand the educational curriculum policies and the influence of capitalism; 2) Understand the effects of curriculum policies in the classroom; 3) Understand the lines of force that mediate the didactic actions of teachers; 4) To analyze whether teaching practices enhance lives. The research was developed using the cartographic methodology, a fieldwork of sensitive listening, which presupposes a proximity to people, situations and paths of intervention. To this end, the instruments used were maps, through which all aspects involving the school space, in the assemblages and in the lines of forces were recorded. From the theoretical-conceptual and analytical point of view, the study is situated in the horizon of the philosophy of difference and, for this reason, the contributions of Gilles Deleuze and Félix Guattari (1995) were chosen. The fundamental categories are: educational policy, curriculum, agency, rhizome, physical education and teaching practice. The research shows as a result that the City Curriculum of physical education produces other effects in the teaching practice, distancing itself from the guidelines contained in it and the school and the teachers maintain the projects and practices independently of the curricular guidelines. It was found that educational policies, as well as discourses, laws and capitalism influence school practices, and the curriculum are only part of this effect. What justifies this research is the fact that its results can contribute to the deepening of curricular studies and specifically that of physical education.